Acute kidney injury in critically ill obstetric patients: a cross-sectional study in an intensive care unit in Northeast Brazil - Silva Junior,Geraldo Bezerra da (2017)
Abstract Introduction: Acute kidney injury (AKI) is a complication still poorly studied in the setting of obstetric patients, which is associated with increased mortality. Objective: The aim of this study was to investigate the frequency and risk factors of AKI among critically ill obstetric patients. Methods: A cross-sectional study was conducted with all patients admitted to an intensive care unit (ICU) due to obstetric complications, in Fortaleza, Brazil, in the period between January 2012 and December 2014. AKI was defined according to AKIN criteria. Results: A total of 389 patients were included, aged between 13 and 45 years. The main causes of ICU admission were pregnancy-related hypertensive syndromes (54.5%), hemorrhage and hemorrhagic shock (12.3%), heart diseases (9.0%), respiratory insufficiency (8.2%) and sepsis (5.4%). AKI was found in 92 cases (24%), and this was the most frequent complication. General mortality was 7.5%, and mortality due to AKI was 21% (p = 0.0007). In the multivariate analysis, risk factors for AKI were cesarian delivery (95% CI = 0.23-0.85, p = 0.01) and thrombocythopenia (95% CI = 1.50-4.36, p = 0.001). AKI was an independent risk factor for death (OR = 6.64, 95% CI = 3.11-14.15, p < 0.001). Conclusion: AKI was the main complication among critically ill obstetric patients and it was associated with increased mortality. Most cases were associated with pregnancy-related hypertensive disorders, which are complications that can be easily identified and treated during prenatal care.